Return to Traditional Wisdom in Controlling Maize Pests in Molamahu, Gorontalo, Indonesia - Hunowu, Momy A.; Rahman, Abdul; Daulay, Pardamean; Fadhilah, Amir; Pakuna, Hatim Badu (JSW (Jurnal Sosiologi Walisongo), 2024)
Government programs in agriculture, such as extension and seed and fertilizer assistance, have increased maize production, but also threaten the preservation of traditional wisdom. This article discusses intractable pest infestations as a major problem in maize farming in Molamahu Village, Gorontalo Regency, Gorontalo Province. Although many agricultural technologies have been developed, they have not been able to effectively control these pests. This study aims to explore the use of traditional methods by farmers in overcoming pest problems, as well as to demonstrate the effectiveness of local wisdom in this context. A qualitative approach was used by interviewing senior farmers and observing the practices of young farmers. The results of this study present clear and structured findings regarding the effectiveness of traditional methods in controlling maize pests. This study found that some traditional methods previously considered irrational turned out to have a robust scientific basis. These results confirm that local knowledge has great potential to strengthen eco-friendly pest control strategies in maize farming. The finding in this research underscores the importance of recognizing and utilizing local wisdom in the development of sustainable agricultural technology.